If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + 5x)(3 + 6x) = 0 Multiply (3 + 5x) * (3 + 6x) (3(3 + 6x) + 5x * (3 + 6x)) = 0 ((3 * 3 + 6x * 3) + 5x * (3 + 6x)) = 0 ((9 + 18x) + 5x * (3 + 6x)) = 0 (9 + 18x + (3 * 5x + 6x * 5x)) = 0 (9 + 18x + (15x + 30x2)) = 0 Combine like terms: 18x + 15x = 33x (9 + 33x + 30x2) = 0 Solving 9 + 33x + 30x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(3 + 11x + 10x2) = 0 Factor a trinomial. 3((3 + 5x)(1 + 2x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(3 + 5x)' equal to zero and attempt to solve: Simplifying 3 + 5x = 0 Solving 3 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = 0 + -3 5x = 0 + -3 Combine like terms: 0 + -3 = -3 5x = -3 Divide each side by '5'. x = -0.6 Simplifying x = -0.6Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5Solution
x = {-0.6, -0.5}
| -9n+5=50 | | 208=2x+8(-4-4x) | | 2x+5=3y+3 | | 6.08+x=10 | | 6.0+x=10 | | 4y-10c=20 | | 2=.71*3 | | 9876543210987654321+abcdefghijklmnopqrstuvwxyz=21 | | (5w+4)(7+w)=0 | | 3x^7+fs=5 | | 6+9=12 | | 5x+9845739457=2 | | 6x-19=x+10 | | 13s-31=9 | | 4x^3-2/x^4 | | X+4x-8.2=16-3x | | y=0.55x+1.75 | | (5w-1)(w+3)=0 | | Dr/t | | x+(7+x)=170 | | (1/2)ln9 | | 30*.25= | | X1/2=7 | | X(m+n)-3(m+n)=0 | | -28=-8x+4 | | .59*180= | | -2=r-2/2 | | ln(x^2-9)-ln(x+3)=2 | | 2b^2=144-b^2 | | 28=21*x | | 2b^2=144-2b^2 | | -x+3y=-25 |